The Influence Of Social Presence On Impulsive Behavior Buy Gen Z On Live Streaming E-Commerce Shopee With Sor Framework - Elsa Christy Gumay; Satria Bangsawan; Dorothy Rouly H. Pandjaitan (Journal of Social Research, 2024)
The rapid development of the internet in Indonesia has driven the growth of e-commerce businesses, with this phenomenon being a major factor in the emergence of live streaming e-commerce features. There exists a social presence in live streaming e-commerce, which is the ability to interact directly with viewers, thus prompting unplanned purchases (Impulsive Buying). In Indonesia, Gen Z tends to engage in impulsive buying, especially when shopping online. The need for instant gratification and the convenience of online shopping further fuel this behavior, often resulting in unplanned and impulsive purchases. Therefore, this study aims to analyze the influence of social presence on impulsive buying in live streaming e-commerce among Gen Z. Using dimensions such as broadcaster's social presence, viewer's social presence, live streaming social presence, arousal, and pleasure. Thus, this research examines the impact of social presence that may affect impulsive buying on Shopee. This study adopts a quantitative research approach using Structural Equation Model (SEM) with AMOS application. Data collection involves quantitative methods through questionnaires and SEM analysis. The research findings indicate that the overall Structural Equation Modeling (SEM) supports the current model, where impulsive buying dimensions have a positive and significant influence from broadcaster's social presence, viewer's social presence, live streaming social presence, arousal, and pleasure. This study is expected to provide theoretical and practical insights into how marketers can effectively plan and implement strategies in live streaming e-commerce. Keywords: e-commerce, marketing, social presence, impulsive buying, Gen Z, Structural Equation Modeling (SEM).